Paradigm shift in manual therapy? Evidence for a central nervous system component in the response to passive cervical joint mobilisation - Schmid, A.; Brunner, F.; Wright, Tony; Bachmann, L. (Churchill Livingstone, 2008)
Segmental neurological modulation, neural hysteresis and biomechanical effects have been proposed as mechanisms underpinning the effects of manual therapy. An increasing number of studies hypothesise activation of the central nervous system resulting in a non-segmental hypoalgesic effect with concurrent activation of other neural pathways as a potential mechanism of action. Whether this model is consistent with the current literature is unknown. This systematic review aims to assess the consistency of evidence supporting an involvement of supraspinal systems in mediating the effects of passive cervical joint mobilisation. We searched randomised trials in three electronic databases from inception to November 2007, without language restriction, and checked reference lists of included studies. We assessed study validity and extracted salient features in duplicate. Fifteen studies met our inclusion criteria. The overall quality was high. We found consistency for concurrent hypoalgesia, sympathetic nervous system excitation and changes in motor function. Pooling of data suggested that joint mobilisation improved outcomes by approximately 20% relative to controls. This specific pattern suggests that descending pathways might play a key role in manual therapy induced hypoalgesia. Our review supports the existence of an alternative neurophysiological model, in which passive joint mobilisation stimulates areas within the central nervous system. © 2008 Elsevier Ltd. All rights reserved.